2008
DOI: 10.1098/rstb.2008.0051
|View full text |Cite
|
Sign up to set email alerts
|

Fission and fusion of Darwin's finches populations

Abstract: This study addresses the causes and evolutionary consequences of introgressive hybridization in the sympatric species of Darwin's ground finches (Geospiza) on the small island of Daphne Major in the Galápagos archipelago. Hybridization occurs rarely (less than 2% of breeding pairs) but persistently across years, usually as a result of imprinting on the song of another species. Hybrids survive well under some ecological conditions, but not others. Hybrids mate according to song type. The resulting introgression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
165
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(169 citation statements)
references
References 89 publications
4
165
0
Order By: Relevance
“…A critical observation is that bats of the genus Artibeus are one of the youngest and most specious lineages of the family Phyllostomidae (46,47). Thus, the patterns of differential rates of reproductive isolation described herein are comparable to empirical studies of young radiations that have identified similar evolutionary patterns regarding the presence/absence of pre-and postmating isolating mechanisms and introgressive hybridization (48)(49)(50).…”
Section: Discussionsupporting
confidence: 65%
“…A critical observation is that bats of the genus Artibeus are one of the youngest and most specious lineages of the family Phyllostomidae (46,47). Thus, the patterns of differential rates of reproductive isolation described herein are comparable to empirical studies of young radiations that have identified similar evolutionary patterns regarding the presence/absence of pre-and postmating isolating mechanisms and introgressive hybridization (48)(49)(50).…”
Section: Discussionsupporting
confidence: 65%
“…Evidence for divergent selection promoting this process (rather 13 than genome-wide drift) is bolstered if: (1) gene flow is still appreciable, (2) genome-wide 14 differentiation is correlated with environmental differences or traits under divergent selection 15 (i.e., genome-wide 'isolation-by-adaptation', IBA) 11,12 , and (3) genome-wide responses to 16 selection are confirmed with experiments [13][14][15] . Genome-wide differences have been 17 documented in herring 16 , mosquitoes 17 , and apple-maggot flies 10,14 , and genome-wide IBA has 18 been reported in many organisms 11,12 . Notably, theory predicts genomic differentiation can be 19 promoted by polygenic adaptation 3 , epistasis 18 , the coupling of differentiation across loci (as in 20 hybrid zone theory) 19 , and mate choice 20,21 .…”
mentioning
confidence: 99%
“…However, in one case, e.g., a male specimen in the series of C. (N.) nigripilosus from Pinta has particularly weakly pigmented wings and genitalia that resemble those of C. (N.) nigripilosus. As in some species of Darwin's fi nches on the Galápagos (Grant and Grant 2008), there may be a low incidence of hybridization between the Chrysopodes species.…”
Section: Discussionmentioning
confidence: 99%